2021
DOI: 10.24160/0013-5380-2021-6-51-61
|View full text |Cite
|
Sign up to set email alerts
|

On Identifying and Calculating Electricity Losses with Automated Metering Systems in Distribution Networks in Case of Unauthorized Consumption

Abstract: A 0.4 kV distribution network equipped with an automated information and measurement electricity metering system is considered. It is assumed that the metering system receives data on active and reactive power, and on the effective voltage values that correspond to the same time interval and are received at the distribution network beginning and from all subscribers. It is also assumed that the impedances of the phase wires are the same for each inter-subscriber section of the network, but differ from the impe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As is known, electricity losses in low-voltage distribution networks are caused by such main factors as: current and voltage unbalance [5,17]; unauthorized electricity consumption (theft) in PDNs [14,18]; nonlinear properties of loads of network consumers [17,19]; exceeded critical levels of wear of wires of backbone network lines. These factors cause the networks to deviate from their rated operating conditions.…”
Section: Structure and Tasks Of Conventional Asemmsmentioning
confidence: 99%
See 1 more Smart Citation
“…As is known, electricity losses in low-voltage distribution networks are caused by such main factors as: current and voltage unbalance [5,17]; unauthorized electricity consumption (theft) in PDNs [14,18]; nonlinear properties of loads of network consumers [17,19]; exceeded critical levels of wear of wires of backbone network lines. These factors cause the networks to deviate from their rated operating conditions.…”
Section: Structure and Tasks Of Conventional Asemmsmentioning
confidence: 99%
“…The practice of their use has shown that they fail to adequately ensure the desired level of electricity losses, since these automated systems are mainly designed for electricity revenue metering. Analysis indicates that to significantly reduce electricity losses in the PDN it is necessary to additionally perform the optimization of operating conditions of facilities [5][6][7][8], diagnostics of critical states of distribution grids [9][10][11], including the identification of places of unauthorized consumption (theft) of electricity [12][13][14], and the monitoring of electricity losses [15,16] in real time. The existing (conventional) ASEMMs do not address this set of tasks.…”
Section: Introductionmentioning
confidence: 99%